Motives and Correlates of Anabolic-Androgenic Steroid Use With Stimulant Polypharmacy. (June 2020) - Zahnow, Renee; McVeigh, Jim; Bates, Geoff; Winstock, Adam R.
Individuals who use anabolic-androgenic steroids (AAS) may engage in concurrent psychoactive drug use recreationally and/or as an additional training aid. Aside from cannabis, individuals who use AAS most commonly report concurrent use of stimulants such as amphetamines and cocaine. In this study, we examine demographic characteristics, frequency of heavy drinking, and nightclubbing in a sample of 993 men from the Global Drug Survey 2015 who reported both AAS and psychoactive drug use before exploring the relationship between motivation for AAS use and the propensity to concurrently engage with stimulant-type substances. Results of a logistic regression analysis suggest that the propensity for concurrent use of AAS and stimulants is greater when AAS use is motivated by weight loss goals, while performance goals are associated with reduced odds of concurrent stimulant use. Identifying individuals who are at risk of polydrug use and associated harms can inform targeted harm reduction strategies.